Dariusz Brodka y Joanna Janik-Sławomir Sprawski (eds.), Freedom and Its Limits in the Ancient World, Cracovia, Jagiellonian University Press, 2003 (= Electrum. Studia z historii starożytnej, vol. 9) (Minerva. Revista de Filología Clásica, 2019)
Reseña de Dariusz Brodka y Joanna Janik-Sławomir Sprawski (eds.), Freedom and Its Limits in the Ancient World, Cracovia, Jagiellonian University Press, 2003 (= Electrum. Studia z historii starożytnej, vol. 9)